Darwin's Warm Little Pond: A One‐Pot Reaction for Prebiotic Phosphorylation and the Mobilization of Phosphate from Minerals in a Urea‐Based Solvent. (6th October 2016) - Burcar, Bradley; Pasek, Matthew; Gull, Maheen; Cafferty, Brian J.; Velasco, Francisco; Hud, Nicholas V.; Menor‐Salván, César
Abstract: The poor reactivity of insoluble phosphates, such as apatite‐group minerals, has been a long‐appreciated obstacle for proposed models of prebiotic organophosphate formation. This obstacle presents a significant challenge to the nascent development of an RNA world and other models for the origins of life on Earth. Herein, we demonstrate that a scenario based on the formation of a urea/ammonium formate/water (UAFW) eutectic solution leads to an increase in phosphorylation when compared to urea alone for phosphate sources of varying solubility. In addition, under evaporative conditions and in the presence of MgSO4, the UAFW eutectic mobilizes the phosphate sequestered in water‐insoluble hydroxyapatite, giving rise to a marked increase in phosphorylation. These results suggest that the prebiotic concentrations of urea in a geologically plausible evaporitic environment could solve the problem of organic phosphorylation on a prebiotic Earth.